2016
DOI: 10.1038/srep37803
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the interaction of the ribosomal P stalk protein P2 with a type II ribosome-inactivating protein ricin

Abstract: Ricin is a type II ribosome-inactivating protein (RIP) that depurinates A4324 at the sarcin-ricin loop of 28 S ribosomal RNA (rRNA), thus inactivating the ribosome by preventing elongation factors from binding to the GTPase activation centre. Recent studies have disclosed that the conserved C-terminal domain (CTD) of eukaryotic ribosomal P stalk proteins is involved in the process that RIPs target ribosome. However, the details of the molecular interaction between ricin and P stalk proteins remain unknown. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 28 publications
(32 reference statements)
0
64
0
Order By: Relevance
“…The C-terminal ends of the ribosomal stalk P proteins interact with a small well-defined hydrophobic pocket on the face of RTA opposite to the active site [ 27 , 28 ]. We show here that peptides derived from the conserved CTD of P proteins can disrupt RTA–ribosome interactions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The C-terminal ends of the ribosomal stalk P proteins interact with a small well-defined hydrophobic pocket on the face of RTA opposite to the active site [ 27 , 28 ]. We show here that peptides derived from the conserved CTD of P proteins can disrupt RTA–ribosome interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The longest peptide tested was P11 because this is the smallest peptide reported to inhibit the activity of Stx1 [ 6 ]. Since the C-terminal end of this peptide is critical for RTA interaction [ 27 , 28 ], we deleted one amino acid at a time starting from the N-terminal end. We found that the longer peptides had higher affinity and inhibitory activity compared to the shorter peptides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations